Designing historical building Melaka into tealive corporate and packaging design Melaka branch / Anis Shafiyyah Mohamad Yusof - Mohamad Yusof, Anis Shafiyyah (2018)
This research is to study around the element of historical building to be applying into Tealive corporate and packaging design Melaka branch. However, people nowadays lack knowledge about history in Malaysia, thus they less promotion in packaging design related to Melaka, most of the packaging product they don’t have any packaging design that related to history. And also about the packaging, the packaging didn’t have any promotion, so researcher choose Tealive company because tealive company is the new rebranding company and the name Tealive itself already well known, so that the big chance of people to get know about the company and the graphic design to be apply. And the reason researcher choose Melaka Historical Building as my element because, as we know Melaka rich with history in Malaysia as Melaka was award as World Heritage site, and there so much information, knowledge for our people or tourist to get know more about Melaka. It’s also highlighting something new about the place itself and can also be called as a new marketing idea. As the objective of this research is to study the consumer perception on Tealive graphic design that related to the Melaka Historical building, to re-promote the history of building in Melaka and to suggest new graphic design of historical building for Tealive company. For this survey researcher will use Quantitative method. In this research it will be used to quantify Melaka Heritage and Historical. The data collection method includes surveys that will be distributed through online. Researcher have finalized all thing that will be such as poster design, kiosk, Uniform for staff, design cup packaging with element of Historical Melaka and food truck. And all the item that have been designed have the meaning and significant about the historical of Melaka. And Maybe for next researcher can do concept design for every state in Malaysia, same like Melaka, for example, Tealive Penang do the design what the iconic of Penang and can implement in new concept for Penang branch and also for Kuala Lumpur, Selangor, Terengganu, Kelantan, Perlis, Kedah, Negeri Sembilan, Johor, Pahang, Sabah and Sarawak.